2013
DOI: 10.1038/gim.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of left ventricular mass in untreated men and in men treated with agalsidase-β: data from the Fabry Registry

Abstract: Fabry disease (FD) (OMIM 301500) is a rare disorder in which globotriaosylceramide and other glycosphingolipids accumulate within lysosomes because of insufficient activity of α-galactosidase A. 1,2 Over time, the glycosphingolipid substrate progressively accumulates within blood vessels and various other cell types throughout the body. The initial signs and symptoms of FD frequently include neuropathic pain in the extremities, hypohidrosis, angiokeratomas, and gastrointestinal discomfort. 3 Over a period of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 31 publications
0
60
1
7
Order By: Relevance
“…The most common cardiac manifestation of Fabry disease is hypertrophic cardiomyopathy 46. LVH is an important risk factor for predicting cardiac events (heart failure and myocardial infarction) in Fabry disease 43 47. Reduction of LV mass has been associated with improved outcomes in Fabry disease; a 3-year study in patients with Fabry disease without myocardial fibrosis found that post-treatment reductions in LV mass were associated with improvement in stress exercise 48.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cardiac manifestation of Fabry disease is hypertrophic cardiomyopathy 46. LVH is an important risk factor for predicting cardiac events (heart failure and myocardial infarction) in Fabry disease 43 47. Reduction of LV mass has been associated with improved outcomes in Fabry disease; a 3-year study in patients with Fabry disease without myocardial fibrosis found that post-treatment reductions in LV mass were associated with improvement in stress exercise 48.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac complications are common and the main cause of death in FD [33]. The most frequent cardiac manifestation is LVH, an important risk factor for cardiac events [34]. Of the patients initially diagnosed with hypertrophic cardiomyopathy, 3.9-12% are eventually found to have FD.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient showed echocardiographical signs of LVH, whereby the thickness of the IVS and the LVPW after 10 years of ERT was normal. As is repeated in the bibliography, an increase in the thickness of the IVS, LVPW, and LVMI is related to age, justified by the fact that the only patient with signs of LVH was the oldest in our series (Germain et al 2013). Agalsidase Beta has proved to be effective in reducing left ventricular mass in patients who commenced ERT between the ages of 18 and 30 according to a recent survey conducted by the Fabry Registry (Germain et al 2013).…”
Section: Discussionmentioning
confidence: 90%